TIPE-TIPE STOMATA TUMBUHAN FAMILIA ASPARAGACEAE SEBAGAI BAHAN AJAR PENGAYAAN ANATOMI TUMBUHAN DALAM BENTUK BOOKLET - Eka Wati, Leoni Dea; Amintarti, Sri; Rezeki, Amalia (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Many plants of the Asparagaceae family are found in the Faculty of Teacher Training and Education environment of Lambung Mangkurat University, but many students do not know the types of stomata. This research has the purpose of describing the types of stomata of the Asparagaceae family found in the Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin, and describing the quality of the booklet development results based on suitability tests, appropriateness tests, and readability tests. Booklet development uses the 4-D model by Thiagarajan is limited to the Develop step this is limited to validation tests and readability tests and the Dissemination stage is limited and simple. The subjects of research and booklet development were 2 lecturers and 9 students who had passed the Plant Anatomy course in Biology Education, Lambung Mangkurat University, Banjarmasin. The results of the study found 3 types of stomata from 8 species of plants in the Asparagaceae family, namely the type of stomata according to Stebbins & Khush (1961), namely: 1) Type 2 is found on Mother-In-Law's Tongue (Sansevieria trifasciata), Large Agave (Agave salmiana), Yellow Leaf Agave (Furcraea foetida), Mother-in-law's tongue (Sansevieria hyacinthoides) and American Agave (Agave americana) 2). Type 3 is found in Hanjuang (Cordyline fruticosa), 3) Type 4 is found in Manggar (Dracaena marginata) and Drakaena (Dracaena reflexa). Suitability test results attained an average score of 4.38 (very appropriate), the feasibility test attained an average score of 4.36 (very feasible), and the students' readability test attained an average score of 4.53 (very good).